2021
DOI: 10.3390/foods10030583
|View full text |Cite
|
Sign up to set email alerts
|

Valle Agricola Chickpeas: Nutritional Profile and Metabolomics Traits of a Typical Landrace Legume from Southern Italy

Abstract: Chickpea (Cicer arietinum L.) from Valle Agricola is a legume cultivated in Southern Italy whose intake is strictly linked to rural traditions. In order to get new biochemical insight on this landrace and to promote its consumption and marketing, nutritional values (moisture content, total proteins, lipids, total and free amino acids) and metabolic traits are deeply investigated. Valle Agricola chickpea is nutritionally rich in proteins (19.70 g/100 g) and essential amino acids (7.12 g/100 g; ~40% of total). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Generally, the crude protein content of the different chickpeas represents 12% to 30% of the seeds, with an average value that is commonly 2–3 times higher than that of cereal grains (Wood & Grusak, 2007 ). In this study, the average amounts of protein from the Muying‐1, Keying‐1, Desi‐1, and Desi‐2 were higher than that from Merella chickpeas (15.70 g/100 g) (Landi et al, 2021 ) and other legumes such as common bean and Bambara groundnut accessions (Baptista et al, 2017 ). Several studies have reported that true protein digestibility, biological value, net protein utilization, and protein efficiency ratio of chickpeas are higher than those of most legumes including soybeans (Dadon et al, 2017 ; Khan et al, 1979 ; Liu et al, 2008 ).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Generally, the crude protein content of the different chickpeas represents 12% to 30% of the seeds, with an average value that is commonly 2–3 times higher than that of cereal grains (Wood & Grusak, 2007 ). In this study, the average amounts of protein from the Muying‐1, Keying‐1, Desi‐1, and Desi‐2 were higher than that from Merella chickpeas (15.70 g/100 g) (Landi et al, 2021 ) and other legumes such as common bean and Bambara groundnut accessions (Baptista et al, 2017 ). Several studies have reported that true protein digestibility, biological value, net protein utilization, and protein efficiency ratio of chickpeas are higher than those of most legumes including soybeans (Dadon et al, 2017 ; Khan et al, 1979 ; Liu et al, 2008 ).…”
Section: Resultsmentioning
confidence: 59%
“…The contents of EAA in the four chickpea species were higher than those in field peas (Pisum sativum L.) (6.62 g/100 g) and hull-less barley (3.23 g/100 g) (Bai et al, 2018;Witten et al, 2018). In addition, the amounts of EAAs in Muying-1 and Keying-1 chickpeas were also higher than those in Valle Agricola chickpeas (7.12 g/100 g) determined by Landi et al (2021).…”
Section: Amino Acid Composition Analysismentioning
confidence: 66%
“…The freeze-dried powder was subjected first to ethanol precipitation using 80% cold ethanol (1.0 mL), in the presence of nor -leucine (200 nmol) as internal standard, dissolved with a Teflon pestle, and centrifuged at 14,000× g at 4 °C. The supernatant was lyophilized, treated with 3% sulfosalicylic acid (500 μL) to precipitate any protein fraction still present, and recentrifuged [ 29 , 30 ]. Aliquots of samples (generally 30 μL) were directly analysed on a Biochrom-30 amino acid analyser (Biochrom, Cambridge, UK), equipped with a post-column ninhydrin derivatization system [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, unavailable carbohydrates, including resistant starch, pectin, cellulose, and oligosaccharides, remain undigested, contributing to the dietary fber content [22]. Notably, chickpeas contain several types of sugars, including glucose (0.05 to 0.06%), fructose (0.31 to 0.35%), maltose (0.33 to 0.35%), and sucrose (3.10 to 4.41%), each with distinct metabolic actions in the human body [11,[23][24][25][26][27][28][29]. Glucose, a monosaccharide, serves as a primary energy source and can be used immediately or stored as glycogen [30].…”
Section: Nutritional and Chemical Composition Of Chickpeamentioning
confidence: 99%